Impact of channel nanostructures of porous carbon particles on their catalytic performance - Oh, Hyunkyu; Lee, Young Jun; Kim, Eun Ji; Park, Jinseok; Kim, Hee-Eun; Lee, Hyunsoo; Lee, Hyunjoo; Kim, Bumjoon J. (Royal Society of Chemistry, 2024)
Mesoporous carbon particles have great potential due to their unique structural properties as support materials for catalytic applications. Particle shapes and channel nanostructures of mesoporous carbon particles can determine the reactant/product transport efficiency. However, the role of the channel nanostructure in the catalytic reaction has not been much explored. Herein, we introduce a facile method to fabricate a series of porous carbon particles (PCPs) with controlled channel exposure on the carbon surface and investigate the impact of the channel nanostructure of the PCPs on the catalytic activity. By employing a membrane emulsification method with a controlled solvent evaporation rate, we fabricate block copolymer (BCP) particles with uniform size and regulated degrees of cylindrical channel exposed to the particle surface. Followed by the carbonization of the BCP particles, a low amount (1.3 wt%) of Pt is incorporated into the PCP series to investigate the impact of channel nanostructures on the catalytic oxidation reaction of o-phenylenediamine (OPD). Specifically, PCP featuring highly open channel nanostructures shows a high reaction rate constant of 0.154 mM-1 s-1 for OPD oxidation, showing 5.5 times higher catalytic activity than those of closed channel nanostructures (0.028 mM-1 s-1). This study provides a deeper understanding of the impact of channel nanostructure within mesoporous carbon particles on catalytic activity. We produce a series of porous carbon particles (PCPs) with controlled channel nanostructures, and systematically investigate the structure-property relationships and catalytic performance of these particles.